Management of water resources in Iraq Proposed problems and solutions (Journal of the College of Basic Education, 2022)
This study dealt with one of the most problems facing Iraq for several decades, and it is expected that this problem will continue for the coming years in the event that no real and effective solutions are found for it, namely the problem of the decline of Iraqi water resources, which began since the seventies with the start of the giant projects of the riparian countries on the rivers The Tigris and Euphrates and its continuation until the present time, but it is not the only reason for the exacerbation of this problem. Rather, several other internal and external causes have combined with it, some of which are natural and some of which are human. To the need to develop the available water resources, manage them well and exploit them, taking into account the size of supply and demand, and take advantage of non-traditional water sources to cover the deficit, especially in the agricultural and industrial side.